Strategi Emotion Focused Coping Untuk Meningkatkan Wellbeing Pada Siswa SMA - Emiyani, Nurul; Saputra, Wahyu Nanda Eka (IJoCE: Indonesian Journal of Counseling and Education, 2024)
Wellbeing is a condition where students experience psychological well-being, marked by feelings of happiness and meaning. Stress is one of the factors that affect wellbeing, and one of the strategies used to cope with stress is coping strategies. Emotion-focused coping strategies focus on managing emotions. These strategies can help students understand and accept their emotions, develop emotional regulation skills, and build better relationships with others. The purpose of this study is to offer an alternative approach to improving the wellbeing of students experiencing stress through emotion-focused coping strategies, thereby enhancing their psychological well-being. Specific strategies considered effective in managing stress and improving well-being include distancing, self-control, accepting responsibility, escape-avoidance, and positive reappraisal